Higher education and pandemic: Contributions from the critical perspective of university students - Pastor Yuste, Raquel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The pandemic caused by COVID-19 led educational institutions to suspend all types of face-to-face activity. Higher education began to develop in digital contexts, which meant a redesign in terms of resources, instruments, modes, action strategies and measures to be implemented in the teaching-learning process. This study analyses, from a qualitative perspective, the visions of students on university teaching in pandemic contexts. The results show the differential perspective of the students, -enthusiastic, critical, condescending and nostalgic- about the higher education, inresponse to their university experience, lived in contexts of profound exceptionality.